A Cooperative Approach to Reduce Water Pollution Abatement Cost in an Interjurisdictional Lake Basin1. (18th November 2013) - Zhao, Laijun; Huang, Wei; Gao, H. Oliver; Xue, Jian; Li, Changmin; Hu, Yue
Abstract A cooperative approach via transfer fee was developed to improve the cost‐effectiveness of water pollution control in interjurisdictional lake basin management in China. Different from the existing literature that studies water quality trading and pollution reduction at micro levels (i.e., focusing on enterprises and firms), this article explores cooperative pollution reduction strategies from a macro level, targeting multiple jurisdictional regions. The merits of this new approach include: (1) improving the cost‐effectiveness of pollution reduction by making use of the cost differentiation in pollution reduction between industries and municipal sewage plants, and between different administrative areas; (2) managing payments for ecosystem services by horizontal transfer payment; and (3) incorporating the concepts of game, cooperation, coordination, and watershed‐based management in implementation. For empirical demonstration, a bilevel optimization model was built and calibrated using the 2005 data of the Lake Tai basin to work out the optimal solutions for cooperative chemical oxygen demand (COD) reduction. Results show that policies based on this new approach can significantly reduce the overall COD abatement costs for the basin as well as the individual jurisdictional regions compared to the current practice.